Bicarbonate-activated persulfate oxidation of acetaminophen. (1st June 2017) - Jiang, Mengdi; Lu, Junhe; Ji, Yuefei; Kong, Deyang
Abstract: Persulfate (PS) is widely used as an oxidant for in situ chemical remediation of contaminated groundwater. In this study we demonstrated for the first time that PS could be activated by bicarbonate. Acetaminophen was used as the probe compound to examine the reactivity of PS/bicarbonate system. It was found that acetaminophen could be effectively transformed and the reaction rate appeared pseudo-first-order to the concentrations of both acetaminophen and PS. Radical scavenger tests indicated that neither free radicals (SO4 - and HO) nor superoxide (O2 - ) was responsible for acetaminophen transformation. Generation of singlet oxygen ( 1 O2 ) was verified using furfuryl alcohol (FFA) as a probe. Formation of 1 O2 was further quantified in D2 O fortified solution based on kinetic solvent isotopic effect (KSIE) but it was found that 1 O2 contributed only 51.4% of the total FFA transformation. The other 48.6% was presumed to be ascribed to the reaction with peroxymonocarbonate (HCO4 − ). However, the transformation of acetaminophen was mostly due to the reaction with HCO4 − but not 1 O2 . Instead of degradation, HCO4 − oxidized acetaminophen via a one-electron abstraction mechanism resulting in the generation of acetaminophen radicals which coupled to each other to form dimers and trimers. HCO4 − also hydrolyzed rapidly to form hydrogen peroxide (H2 O2 ) which led to the formation of 1 O2, during which O2 - was a key intermediates. Because bicarbonate is ubiquitously presented in groundwater, the findings of this research provide important insights into the fundamental processes involved in PS oxidation in subsurface. Graphical abstract: Highlights: Persulfate can be activated by bicarbonate to form HCO4 − . HCO4 − hydrolyzes rapidly and leads to the formation of 1 O2 . Oxidation of acetaminophen was mostly due to the reaction with HCO4 − . Acetaminophen was transformed via oxidative coupling mechanism.